2006
DOI: 10.1103/physrevlett.96.052501
|View full text |Cite
|
Sign up to set email alerts
|

Transition Probabilities inPr134: A Test for Chirality in Nuclear Systems

Abstract: Exited states in 134Pr were populated in the fusion-evaporation reaction 119Sn(19F,4n)134Pr. Recoil distance Doppler-shift and Doppler-shift attenuation measurements using the Euroball spectrometer, in conjunction with the inner Bismuth Germanate ball and the Cologne plunger, were performed at beam energies of 87 MeV and 83 MeV, respectively. Reduced transition probabilities in 134Pr are compared to the predictions of the two quasiparticle + triaxial rotor and interacting boson fermion-fermion models. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(55 citation statements)
references
References 18 publications
2
51
1
1
Order By: Relevance
“…In both nuclei, however, Doppler-shift attenuation method (DSAM) lifetime experiments demonstrated that the B(E2) values in the chiral-candidate doublet bands differ considerably from each other [9][10][11]. Thus, for these nuclei the chiral scenario does not seem to hold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both nuclei, however, Doppler-shift attenuation method (DSAM) lifetime experiments demonstrated that the B(E2) values in the chiral-candidate doublet bands differ considerably from each other [9][10][11]. Thus, for these nuclei the chiral scenario does not seem to hold.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for these nuclei the chiral scenario does not seem to hold. For 134 Pr, several new theoretical attempts have been made to explain the nature of the observed doublet structure [9,[12][13][14], but these have led to different conclusions. They all have concentrated on the doublet structure; however, very recently a third πh 11/2 νh −1 11/2 band was observed in 134 Pr [15] which could be a chiral partner of the previously known πh 11/2 νh −1 11/2 side band.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study of the chiral doublet bands in 103 Rh has shown that the energy separation of these structures depends mainly on the core properties and, to a lesser extent, on the valence quasiparticle coupling [6]. However, the chiral interpretation in the A = 130 region has been questioned due to lifetime measurements [7,8], and it could not be confirmed by lifetime experiments in the nuclei 103 Rh and 104 Rh [9]. In this respect, it is important to understand the necessary conditions leading to the emergence of chiral geometry, one of which is the shape of the corresponding even-even core.…”
Section: Introductionmentioning
confidence: 99%
“…At intermediate spins, there has been much discussion about chirality in odd-odd and even-Z nuclei [12][13][14][15], based on the spin axes of the unpaired proton and neutron and the rotational axis of the core. However, in this regime, in some cases there has been controversy as to the rigidity or softness of the nuclear body leading to the observed structures [16]. At the lowest spins, however, especially in the ground state itself, triaxial structures have typically been ascribed to pronounced γ softness, corresponding to a broad minimum in γ .…”
mentioning
confidence: 99%